Pemberdayaan Masyarakat Melalui Teknologi Pengolahan Ikan Asin Ramah Lingkungan Berbasis Greenhouse - Nurhidayah, Fitriyah; Silalahi, Ronald Maraden P.; Setiawan, Agustinus Agus; Mantofani, Rizal (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
Sumberjaya Village is a coastal community known as a traditional salted-fish production center, supported by abundant marine resources such as anchovy, grouper, tuna, snapper, and shrimp. Despite its potential, the drying process still relies heavily on conventional sun drying, making production vulnerable to weather conditions. During the rainy season, production frequently halts, product quality declines, and community income drops significantly. Through the BIMA Community Service Grant Program, the implementing team introduced an innovative Solar-Powered Greenhouse Dryer to address these challenges. This technology enables year-round drying in a hygienic, efficient, and environmentally friendly manner, producing cleaner and longer-lasting salted fish with higher market value. In addition to technological intervention, the program also provided training in business management, basic financial recording, digital marketing, and product legality assistance, including PIRT, NIB, and halal labeling. This integrated approach strengthened production capacity, enhanced community skills, and reinforced local institutional resilience. Overall, the synergy between appropriate technology and community capacity building has transformed Sumberjaya Village into a model of modern green-technology-based salted-fish processing, serving as a best-practice example of sustainable coastal economic empowerment in Indonesia.